CSI based key generation through OFDM channel in M2M communication - Sakhardande Anuj (2017)
With enhancement in wireless technology, security has become an important part in designing of network. Network security is an important aspect of system administration. We are living in a world where there is access to information anywhere, anytime, be it voice, multimedia or data analytics. This information should be provided to the user with the highest possible security. Thus the information exchanged for communication should be highly secured, authentic and only accessible to the authorised user. Recent research has shown that, this security can be provided through RSS (Received Signal Strength) based key generation techniques for authentication of user. But RSS based key generation technique has a drawback that the key generation rate is very low. RSS based technique is highly applicable for mobile devices. In M2M Communication the devices can be static or mobile based. So we explore a technic which is based on Key generation through CSI (Channel State Information) of a channel. Key generation using CSI information can be efficient in the terms of providing security as they can generate quiet a long key as compared to RSS based technique. We deploy an algorithm as a solution to key generation without using additional hardware for key generation and verify that the malicious user is not able to decode the key sighting to the randomness obtained to our algorithm. The major portion of the algorithm concentrates on making the key random so that the attacker is not able to decode the key within a time span which is vulnerable to the communication. When an attacker tries to use the same algorithm and try to sabotage the communication, due to the property of CSI information of OFDM channel, the generated key will be different. Thus it will not match with the secret key used for actual communication. Hence the user will not be able to hijack the communication.